Análise ambiental em áreas de veredas no curso do córrego correntinho, Miracema do Tocantins-TO - Martins, Wagner Lemos (Universidade Federal do Tocantins, 2020)
This research deals with an environmental analysis of Veredas, located in Correntinho stream, which is located in the city of Miracema do Tocantins about 70 km from Palmas, capital of the state of Tocantins. The present research aimed to analyze the environmental conditions of Veredas of Correntinho stream, located in the city of Miracema do Tocantins (TO). Its main goal is to verify the environmental conditions of Veredas, located in the main course of the stream in question. The methodology adopted was the application of the Normalized Difference Vegetation Index (NDVI), the Normalized Difference Water Index (NDWI), a Rapid Vereda Assessment Protocol (PARV), an analysis of land use and occupation, and at the end, correlate the obtained results. As a result, it was obtained the characterization of the geoenvironmental components in which the thematic maps were generated: geological, geomorphological, pedological, hydrographic. The use of the NDVI tool indicated that the vegetation mass in the course of the Correntinho stream is in several stages. At sample points 1 through 5 it is not impacted, at point 6 impacted and at points 7 through 12 reasonably impacted. Regarding the NDWI tool, they indicate that the wetlands identified in the Correntinho stream, including the Veredas, are equivalent to 944 m² area, and in the application of the PARV it was verified the geoenvironmental conditions of Veredas environment in Correntinho stream course, showing a conservation level at some points in the stream, from the source to the middle course, at some points anthropic interference and other parts that are still conserved but with early stages of degradation. It was also possible to identify the importance of local Veredas as a fundamental element in Cerrado biome that works to regulate the surface water flow, supply the underground aquifer, and alsoas a source of income for local communities that make use of both extractivism and crafts. In general, one can realize the importance of the research, demonstrating the fundamental role of the Veredas of the Correntinho stream for the Cerrado and its environmental conditions related to use and occupation.